Repeatability of Anterior Eye Surface Topography Parameters from an Anterior Eye Surface Profilometer. Issue 10 (8th October 2021) - Niyazmand, Hamed; Read, Scott A.; Atchison, David A.
Abstract : SIGNIFICANCE: Anterior eye shape measurements are important for clinical contact lens fitting. The detailed assessment of measurement repeatability using the Eye Surface Profiler (ESP; Eaglet Eye B.V., AP Houten, the Netherlands) allows for more reliable interpretation of eye surface topography measurements. PURPOSE: This study aimed to determine the repeatability of the ESP for anterior central corneal power and anterior eye surface height measurements. METHODS: A Badal optometer was mounted on the ESP to provide an external fixation target with appropriate accommodation control and refractive correction. Forty-five healthy young adults underwent two sessions of anterior eye measurements, separated by 20 minutes, using the ESP. In each session, three consecutive scans were captured. Sagittal height data were obtained from 8-mm central cornea and from 8- to 14-mm diameter (encompassing the corneal periphery and anterior sclera). Anterior corneal powers were determined from the central cornea. Intersessional and intrasessional repeatability values were determined as coefficients of repeatability and root mean square error differences. RESULTS: Sagittal height intersessional coefficients of repeatability for central nasal (5 μm) and central temporal (7 μm) were better than peripheral nasal (24 μm) and peripheral temporal (21 μm) regions. Sagittal height intrasessional coefficients of repeatability were 9, 8, 28, and 31 μm for central nasal, central temporal, peripheral nasal, and peripheral temporal regions, respectively. Intersessional coefficients of repeatability of mean sphere, 90/180° ( J 0 ) astigmatism, and oblique ( J 45 ) astigmatism were 0.67, 0.22, and 0.13 D, respectively, with corresponding intrasessional coefficients of repeatability of 1.27, 0.21, and 0.27 D. CONCLUSIONS: The modified measuring procedure for the ESP used in this study provides highly repeatable sagittal height measurements in the central cornea but is less repeatable in the corneal periphery and scleral region. Results of the current study can be considered when using ESP in the interpretation of anterior eye surface shape measurements and in contact lens fitting and design.